2015
DOI: 10.1123/jcsp.2015-0005
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Outcome Expectancies and Normative Perceptions of Students Engaged in University Sport in England

Abstract: ?? 2015 Human Kinetics, Inc. Accepted Manuscript version reprinted by permission from Journal of Clinical Sport Psychology, Vol. (1): 59-75, March 2015, doi: https://doi.org/10.1123/jcsp.2015-0005.This study examined whether students engaged in university sport have different drinking outcome expectancies and normative beliefs than students who are not engaged in university sport. A cross-sectional survey of university students in England in 2008???2009 was undertaken. A questionnaire battery, including the Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Whilst no direct comparative data are available for the United Kingdom a study by Southampton Student Union into initiation activities found of those surveyed all stated that their initiation involved alcohol. This combined with the results of a study by Longstaff et al (2015) who found that UK student athletes "consistently reported that they drank significantly more frequently, drank in greater quantities, and were more often drunk than students who were not engaged in university sport" (p. 69), suggests that alcohol may be an important and significant component of British student athletes' initiation practices. In turn, excessive consumption can increase the health risks associated with initiation activities directly and indirectly (Groves, Griggs, & Leflay, 2012).…”
Section: Introductionmentioning
confidence: 76%
“…Whilst no direct comparative data are available for the United Kingdom a study by Southampton Student Union into initiation activities found of those surveyed all stated that their initiation involved alcohol. This combined with the results of a study by Longstaff et al (2015) who found that UK student athletes "consistently reported that they drank significantly more frequently, drank in greater quantities, and were more often drunk than students who were not engaged in university sport" (p. 69), suggests that alcohol may be an important and significant component of British student athletes' initiation practices. In turn, excessive consumption can increase the health risks associated with initiation activities directly and indirectly (Groves, Griggs, & Leflay, 2012).…”
Section: Introductionmentioning
confidence: 76%